Demystifying the belt and road initiative: Scope, actors and repercussion for Europe - Mario Esteban; Yuan Li (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2017)
Despite the high international consensus on the enormous potential of the Belt and Road Initiative for reconfiguring international relations in Eurasia and beyond, and the consequent attention raised by this strategy throughout the world, there are still many unanswered questions. The present paper analyzes the case studies of the Yuxinou (渝新欧) and the Yixinou (义新欧) railway lines to tackle three debates surrounding this initiative: its scope, whether this is a merely economic scheme or also has a geostrategic dimension; its actors, underlining the coordinated action of Chinese central and local authorities; and its implications on EU-China relations, with emphasis on trade imbalances and the consolidation of global value chains. Both secondary and primary sources have been used in this paper, including interviews with relevant officials, business people, and scholars from China, Germany, and Spain.
Keywords: 330; Yuxinou; Yixinou; Belt and Road Initiative; New Silk Road; China-EU relations